Fabrication and characterization of phosphorus-doped diamond field emitters in triode-type field emission arrays - Chen, CF; Tsai, CL; Lin, CL (My University, 2001)
In this work, we present a novel scheme that involves a new fabrication process for gate-structured metal-insulator-semiconductor (MIS) diodes using IC technology. Using a bias-assisted microwave-plasma chemical vapor deposition (BAMPCVD) system to synthesize P-doped emitters completes this process. A comparison of the held emission characteristics of two types of non-doped dendrite-like and P-doped nanotube-like diamond emitters with a 4-mum gate aperture is made. Phosphorus doping can enhance the electrical characteristics by reducing the turn-on voltage and enhancing the emission current density. The turn-on voltage of non-doped and P-doped emitters is 15 and 5 V, respectively. Phosphorus doping can enhance the electrical properties by increasing the emission current, since the field emission current (I-a) of non-doped and P-doped emitters is 4 muA (at V-gc = 45 V) and 322 muA (at V-gc = 120 V), respectively. The emission current of P-doped emitters is approximately 80-fold larger than that of non-doped diamond emitters. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: field emission; diamond; chemical vapor deposition (CVD); n-type doping